Common genetic variation and schizophrenia polygenic risk influence neurocognitive performance in young adulthood. Issue 5 (12th May 2015) - Hatzimanolis, Alex; Bhatnagar, Pallav; Moes, Anna; Wang, Ruihua; Roussos, Panos; Bitsios, Panos; Stefanis, Costas N.; Pulver, Ann E.; Arking, Dan E.; Smyrnis, Nikolaos; Stefanis, Nicholas C.; Avramopoulos, Dimitrios
Abstract : Neurocognitive abilities constitute complex traits with considerable heritability. Impaired neurocognition is typically observed in schizophrenia (SZ), whereas convergent evidence has shown shared genetic determinants between neurocognition and SZ. Here, we report a genome‐wide association study (GWAS) on neuropsychological and oculomotor traits, linked to SZ, in a general population sample of healthy young males (n = 1079). Follow‐up genotyping was performed in an identically phenotyped internal sample (n = 738) and an independent cohort of young males with comparable neuropsychological measures (n = 825). Heritability estimates were determined based on genome‐wide single‐nucleotide polymorphisms (SNPs) and potential regulatory effects on gene expression were assessed in human brain. Correlations with general cognitive ability and SZ risk polygenic scores were tested utilizing meta‐analysis GWAS results by the Cognitive Genomics Consortium (COGENT) and the Psychiatric Genomics Consortium (PGC‐SZ). The GWAS results implicated biologically relevant genetic loci encoding protein targets involved in synaptic neurotransmission, although no robust individual replication was detected and thus additional validation is required. Secondary permutation‐based analysis revealed an excess of strongly associated loci among GWAS top‐ranked signals for verbal working memory (WM) and antisaccade intra‐subject reaction time variability (empirical P  < 0.001), suggesting multiple true‐positive single‐SNP associations. Substantial heritability was observed for WM performance. Further, sustained attention/vigilance and WM were suggestively correlated with both COGENT and PGC‐SZ derived polygenic scores. Overall, these results imply that common genetic variation explains some of the variability in neurocognitive functioning among young adults, particularly WM, and provide supportive evidence that increased SZ genetic risk predicts neurocognitive fluctuations in the general population. © 2015 The Authors American Journal of Medical Genetics Part B: Neuropsychiatric Genetics Published by Wiley Periodicals, Inc.